The Vision of Polish History in Historical Creativity of Celina Bobińska in the Pages of “Nowe Drogi” – Selected Examples - Pasisz, Piotr (Respectus Philologicus, 2018)
[full article in Polish; abstract in English] The article is an attempt to analyse the achievements of Celina Bobińska in the pages of Nowe Drogi, one of the leading magazines of leftist intelligentsia. Bobińska, as a historian, interpreted the main moments of Polish history from the turn of the 18th and 19th century, looking at them through the prism of historical materialism. The analysis will focus on selected articles by Bobińska from the turn of the forties and fifties. The research questions that will be posed are characteristic of historiography historiographer – what was the interpretation of these events and why and what other than theoretical and philosophical assumptions laid at the basis of such a vision of Polish history. Post-war years were a special moment in the history of the Polish intelligentsia, when this layer faced dilemmas of involvement on the side of building a new social order in its material, but also institutional and consciousness aspect. The construction of the latter was especially a task for the intelligentsia, which journalism used to do. Bobińska was one of the leading representatives openly on the side of Marxism (as a certain theory, but also a worldview).